2007
DOI: 10.1136/tc.2007.021477
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden of adult lung cancer and ischaemic heart disease from passive tobacco smoking in China

Abstract: Objective:To address the health hazards tobacco smoking imposes upon non-smokers in China, this paper estimates the burden of diseases in adults from passive tobacco smoking for two major diseases—lung cancer and ischaemic heart disease (IHD).Methods:The disease burden was estimated in terms of both premature mortality and disability adjusted life years (DALYs), a measure that accounts for both the age at death and the severity of the morbidity.Results:Passive smoking caused more than 22 000 lung cancer deaths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 33 publications
0
59
0
1
Order By: Relevance
“…Although only 2.4% of women smoke in China, 72.4% are exposed to SHS, with 38.0% exposed on a daily basis, many of whom do not recognize the dangers of SHS exposure 27 . Consequently, women bear nearly 80% of the burden of disease due to SHS exposure 28 . Children in China with chronic exposure to SHS have respiratory problems that continue into adulthood, including impaired lung function, coughing, sneezing, and phlegm 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Although only 2.4% of women smoke in China, 72.4% are exposed to SHS, with 38.0% exposed on a daily basis, many of whom do not recognize the dangers of SHS exposure 27 . Consequently, women bear nearly 80% of the burden of disease due to SHS exposure 28 . Children in China with chronic exposure to SHS have respiratory problems that continue into adulthood, including impaired lung function, coughing, sneezing, and phlegm 29 .…”
Section: Discussionmentioning
confidence: 99%
“…24 In China, public awareness of the health risks associated with SHS exposure is low. [25][26][27] A Chinese nationally representative household survey reported that, among nonsmokers aged ≥15 years, 556 million (72.4%) were exposed to SHS, and 50% were exposed daily. Exposure in public places, households and indoor workplaces was 72.7%, 67.3% and 63.3% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the incidence of squamous cell carcinoma was 54.5% in male and 15.6% in females. One possible explanation to this tendency is that men have much higher prevalence of smoking than women in China [10][11][12][13][14][15][16][17] . Chinese National Tobacco Prevalence Survey in 2002 reported current smoking prevalence of 57.4% for men and 2.6% for women [14].…”
Section: Discussionmentioning
confidence: 99%